DISCRETE REPRESENTATION MODEL OF MULTIPLY CONNECTED PIPELINES WITH DISTRIBUTED PHYSICAL PROPERTIES - Lyutak, Igor (International Journal of Computing, 2014)
In this paper presented approach of developing chain model which describe distributed physical properties of multiply connected pipeline. It is shown that the digital autoregressive filter can be used to analyze signals of wave propagation in the chain model.